PJEPA Highlights of an initial ex-post review - Medalla, Erlinda M. (2013)
The Philippines-Japan Economic Partnership Agreement (PJEPA), which is considered a "new age" free trade agreement (FTA), is the first and, so far, the only bilateral economic partnership agreement entered into by the Philippines. Beyond the elimination of tariffs on traded goods featured in an FTA, the PJEPA has provisions for fostering the smooth transborder flow of people, capital, and information in areas such as investment, competition, government procurement, trade facilitation, cooperation in science and technology, human resource development, small and medium enterprises, and the environment.

Not quite five years into the implementation of the agreement, what has been PJEPA`s impact on the Philippines thus far? This Policy Note summarizes and updates the main points of a recent PIDS discussion paper on the subject. Given the limited time that has elapsed, it is not possible to undertake a comprehensive assessment. This initial analysis relies on present trends and qualitative factors that already give some indication of the PJEPA`s impact from certain key perspectives.
Keywords: Philippines -- Foreign economic relations -- Japan